Neurotransmitters and Sodium Channelopathies; Possible Link? - Michael F. Hammer; Alejandra D.C. Encinas (Pediatric Neurology Briefs Publishers, 2017)
Investigators from the University of British Columbia, Great Ormond Street Hospital for Children, and the National Hospital reported their findings on neurotransmitter deficiencies in two patients with mutations in voltage-gated sodium genes (SCN2A and SCN8A) discovered by whole exome sequencing.